LGG-42. RECURSIVE PARTITIONING ANALYSIS OF PROGNOSTIC FACTORS FOR PEDIATRIC LOW-GRADE GLIOMAS TREATED WITH RADIATION THERAPY. Issue 2 (22nd June 2018) - Acharya, Sahaja; Ellison, David; Qaddoumi, Ibrahim; Gajjar, Amar; Merchant, Thomas
Abstract: PURPOSE: Pediatric low-grade glioma (PLGG) represents a heterogeneous group of tumors. The purpose of this study was to identify clinical prognostic factors for overall-survival (OS) in PLGG treated with radiation therapy (RT). METHODS: Between 1986 and 2017, 174 patients with non-metastatic, biopsy-proven PLGG were consecutively treated with RT at a single institution. OS was estimated using Kaplan-Meier methods. Prognostic factors were identified using Cox proportional hazards. Recursive partitioning analysis (RPA) was used to stratify patients into high and low-risk prognostic groups. RESULTS: Median follow-up was 11.3 years. Median age was 8.3 years. Common subtypes included: pilocytic astrocytoma (67%), astrocytoma not otherwise specified (12%), and diffuse astrocytoma (DA) (10%). Most were located in the optic pathway/hypothalamus (37%) or thalamus/midbrain (24%). Median tumor dimension was 2.8 cm. On multivariate analysis, tumor size (cm) (Hazard ratio [HR]: 1.81, 95% CI: 1.38-2.37, p<0.001), thalamic/midbrain compared to optic pathway/hypothalamic location (HR: 3.93, 95% CI: 1.17-13.19, p=0.027) and DA compared to pilocytic astrocytoma (HR: 3.33, 95% CI: 1.01-10.97, p=0.048) were independently prognostic for OS. RPA yielded four nodes which were pruned into two groups: low-risk (tumors ≤4.6 cm, non-thalamic/midbrain and non-DA) and high-risk (tumors >4.6 cm or thalamic/midbrain or DA) with 10-year OS of 97% vs. 78% (95% CI: 91%-99% vs. 64%-86%, p <0.001), respectively. CONCLUSION: In progressive PLGG treated with RT, tumor size, thalamic/midbrain location and diffuse histology may stratify patients into prognostic groups. This clinical model requires validation and might be improved with molecular markers to aid therapy selection.